LECT 2 Antagonizes FOXM1 Signaling via Inhibiting MET to Retard PDAC Progression - Li, Xin; Lin, Pingping; Tao, Ye; Jiang, Xin; Li, Ting; Wang, Yunshan; Wang, Chenjing; Cao, Yu (Frontiers in Cell and Developmental Biology, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal cancers with minimally effective treatments, highlighting the importance of developing novel biomarkers and therapeutic targets. Here, we disclosed the mechanisms by which leukocyte cell-derived chemotaxin 2 (LECT2) modulates PDAC development using in vitro and in vivo models. LECT2 is downregulated in metastatic PDACs compared with the primary tumor, and its expression is correlated with multiple clinical pathologic features and prognosis. Its absence promotes multiple malignant behaviors, including cell proliferation, EMT, migration, and invasion. In vivo studies showed that LECT2 overexpression inhibits tumor growth and lung metastasis. Mechanistically, LECT2 inhibits FOXM1 signaling by targeting HGF/MET to retard PDAC progression, revealing LECT2 as a promising biomarker and therapeutic target for PDAC in the future.